(untitled) (International Journal of Occupational Safety and Health, 2017)
Background: Goldsmiths are known for using potent toxic chemicals which pose a health risk to workers which occur either by inhalation or by dermal contact. Chemicals taken up by the body causes damage to vital organs of body such as kidneys, lungs etc., there by affecting their normal physiology and function. Objective: Present study reports the assessment of Nephrotoxicity among goldsmiths who are employed from 4 years-50years in jewellery making units. Methods: The study involved various environmental parameters such as determination of TSPM for air pollutant analysis, biological parameters such as urinary β-2-microglobulin, urinary Creatinine, urinary albumin, urinary total protein concentrations, and serum concentrations of Glutathione-S-Transferase, Catalase, extracellular Super Oxide Dismutase and total protein in both control and test samples. Result: Environmental, biological parameters of exposure and renal dysfunction were examined in a group of goldsmith workers (n=22) and in an un-exposed control group (n=22).The parameters examined were compared between the two groups and related to different exposure parameters. The TSPM concentrations ranged between 75-664 µg/m3. The concentrations of β-2-microglobulin were 0.14-1.2 mg/g of Creatinine, In exposed group Serum concentration of Glutathione-S-Transferase was 1.19 ± 0.48, Catalase 5.1 ± 0.61, extracellular Super Oxide Dismutase 281.2 ± 90.8, and total protein 5.9 ±0.83. However there were no significant changes in the urinary albumin and urinary total protein concentrations between the exposed and the control population.